Analisis Penggunaan Teknologi Digital dalam Berkomunikasi Driver Tour Guide untuk Meningkatkan Pengalaman Wisatawan - I. G. N. P Arimbawa Arimbawa; N.P. Nanik Hendrayanti; I.G.T. Heriawan Heriawan (Jurnal Syntax Admiration, 2024)
This study aims to analyze the use of digital technology in communication between driver tour guides and tourists in Bali, as well as its impact on the tourist experience. This research employs a mixed-method approach, combining quantitative and qualitative methods. The quantitative approach was conducted through a survey of tourists using driver tour guide services in Bali, while the qualitative approach was conducted through in-depth interviews with driver tour guides. Quantitative data were analyzed using correlation analysis and the F-test, while qualitative data were analyzed using thematic analysis techniques.The results indicate that the use of digital technologies, such as mobile applications and chatbots, significantly improves the quality of communication and tourist satisfaction. Correlation analysis shows a very strong relationship between the use of digital technology by drivers and tourist satisfaction (correlation coefficient R = 0.911). The F-test indicates that the effect of digital technology use on tourist satisfaction is significant (F-value = 61.814; p < 0.05). Qualitative findings also reveal that digital technology facilitates more accurate and faster information, thereby enhancing the overall tourist experience.This research provides significant contributions to the development of theory and practice in the tourism field and offers practical recommendations for enhancing tourism services through digital technology.